The Politics of Irish Memory - Pine, E. author. aut Link
IX, 201 p.
Keywords: Irish culture is obsessed with the past, and this book asks why and how. In an innovative reading of Irish culture since 1980, Emilie Pine provides a new analysis of theatre, film, television, memoir and art, and interrogates the anti-nostalgia that characterizes so much of contemporary Irish culture.